Pomoże ktoś? W załączniku
![Pomoże Ktoś W Załączniku class=](https://pl-static.z-dn.net/files/dd2/7f7d48afb960327d98d4d0c7f3259747.jpg)
[tex]a)-\frac{1-2}{2\cdot2} =-\frac{-1}{4} =\frac{1}{4}[/tex]
[tex]b)-\frac{1-(-2)}{2\cdot(-2)} =-\frac{1+2}{-4} =-\frac{3}{-4} =\frac{3}{4}[/tex]
[tex]c)-\frac{1-(-\frac{1}{2} )}{2\cdot(-\frac{1}{2} )} =-\frac{1+\frac{1}{2} }{-1} =-\frac{1\frac{1}{2} }{-1} =1\frac{1}{2}[/tex]
[tex]d)-\frac{1-(-0,2)}{2\cdot(-0,2)} =-\frac{1+0,2}{-0,4} =-\frac{1,2}{-0,4} =3[/tex]